The Effect of Capital Expenditure and Corporate Hedging on Firm Value with Exchange Rate as Moderating Variable: Firm Value - Nuraeni Noviyanti; Iis Ismawati; Rita Rosiana (Journal of Applied Business, Taxation and Economics Research, 2022)
The purpose of this study was to determine the effect of capital expenditure and corporate hedging on firm value, and the effect of the exchange rate on the relationship between capital expenditure and corporate hedging and firm value. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. By using purposive sampling method, obtained 119 companies that meet the criteria as research samples with an observation time of 5 years, so that the total final sample is 595 observational data. This study uses secondary data obtained from the Indonesia Stock Exchange website. In this study, the analysis method is moderated regression analysis (MRA) with testing tools using the IBM SPSS version 25 data processing application. The results of this study indicate that: (1) Capital expenditure has no effect on firm value (2) Corporate hedging has an effect on firm value (3) Exchange rate as a moderating variable cannot moderate the relationship between capital expenditure and firm value (4) Exchange rate as a moderating variable cannot moderate the relationship between corporate hedging and firm value